Revitalising Peninsular Malaysia's agriculture : some areas of scope for better performance - Gibbons, E. T.; Hussein, Mohd Ariff (1986)
Malaysia's 1.9 mn agricultural workforce is characterized by low productivity, well above average age and low educational status. There is a myriad of institutions: the statistical base is weak and out of date; socioeconomists such as farm management and policy specialists are not contributing nearly enough to the identification, definition and solution of the probles. Major diversification into oil palm and the reclamation of 1.2 mn. ha. of the jungle. These advances have been largely nullified by the steep increase in the area of idle land and an almost-complete "productivity stagnation" in most of agriculture. Peninsular Malaysia could, it is argued, increase its agricultural production by 72%.